2019
DOI: 10.1101/792119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alanine, arginine, and proline but not glutamine are the feed-back regulators in the liver-alpha cell axis in mice

Abstract: Aim:To identify the amino acids that stimulate glucagon secretion in mice and whether the metabolism of these relies on glucagon receptor signaling.Methods: Pancreata of female C57BL/6JRj mice were perfused with 19 individual amino acids (1 mM) and secretion of glucagon was assessed using a specific glucagon radioimmunoassay. Separately, a glucagon receptor antagonist (GRA; 25-2648, 100 mg/kg) or vehicle was administered to female C57BL/6JRj mice three hours prior to an intraperitoneal injection of four differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…We were not able to measure glutamine, which has also been implicated. Of interest, a recent study of the effects of amino acids on the isolated perfused mouse pancreas showed that alanine, arginine, and proline in particular, but not glutamine, stimulated glucagon secretion (38).…”
Section: Discussionmentioning
confidence: 99%
“…We were not able to measure glutamine, which has also been implicated. Of interest, a recent study of the effects of amino acids on the isolated perfused mouse pancreas showed that alanine, arginine, and proline in particular, but not glutamine, stimulated glucagon secretion (38).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive glucagon secretion along with α-cell proliferation will follow to execute the functionality of the recently described liver-α-cell axis [7][8][9]13]. Especially, Gln regulates α-cell proliferation and mass via mTOR-dependent nutrient sensing [12,16], whereas Ala, Arg, Cys and Pro, but not Gln, are involved in the acute liver-α-cell axis of female mice [14]. Our previous and present results all demonstrated that excessive glucagon levels are accompanied by α-cell proliferation, and this phenomenon is linked with changes in amino acid levels as well as normal insulin and GLP-1 levels in Gcgr V369M+/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Gcgr knockout or administration of GCGR-blocking antibodies affected serum amino acid availability [7][8][9][10][11]. Circulating amino acids could act as a nutrient sensing circuit between the liver and the pancreas to control glucagon secretion from the α-cell, thereby forming a feedback loop, i.e., liverα-cell axis [7,8,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This was in concert with those changes in the BT-LPS group in the present study. Arginine, proline, and alanine are glucogenic amino acids that also contribute to energy metabolism by increasing some intermediates in the pool of the TCA cycle ( Galsgaard et al, 2019 ; Jiang et al, 2020 ). Combined with a significant or modest increase of fructose-1,6-bisphosphate, d -glyceraldehyde-3-phosphate, and dihydroxyacetone phosphate after LPS challenge, this indicated that the liver might overcome LPS-induced stress by utilizing glucogenic amino acids to synthesize more glucose and to accumulate energy for cellular physiological regulation.…”
Section: Discussionmentioning
confidence: 99%